Effect of Calcium-based Phosphate Binders Versus Sevelamer on Mortality of Patients with Hemodialysis: A Meta-analysis (Iranian Journal of Kidney Diseases, 2022)
Chronic kidney disease is a public health problem. The purpose of this study was to compare the effects of sevelamer and calciumbased binders on mortality of hemodialysis patients. PubMed, EMBASE and Web of Science were searched for related articles published before May 14, 2020. We included six studies with 43330 participants, of which 21147 and 22183 received calciumbased phosphate binders and sevelamer, respectively. In the analysis of unadjusted data, sevelamer could lower cardiovascular mortality. When adjusted HRs was pooled, the cardiovascular mortality did not differ significantly in the sevelamer and calcium-based phosphate binders groups. Additionally, the all-cause mortality rate in sevelamer group was different from that in calcium-based phosphate binders group. However, sevelamer could not lower all-cause mortality in terms of the adjusted data. No significant difference was found in calcium and phosphorus between calcium-based phosphate binders and sevalmer. Sensitivity analysis showed that partial results of the study were inconsistent. There was no difference in the effect of sevelamer and calciumbased phosphate binders on the risk of all-cause mortality in patients with hemodialysis, after adjusting confounders. However, given the instability of the results, the results need to be further confirmed by a large sample and high quality RCTs.  DOI: 10.52547/ijkd.6814